Middle- to late-Holocene storminess in Brittany (NW France): Part I – morphological impact and stratigraphical record. (April 2014) - Van Vliet-Lanoë, Brigitte; Goslin, Jérôme; Hallégouët, Bernard; Hénaff, Alain; Delacourt, Christophe; Fernane, Assia; Franzetti, Marcaurelio; Le Cornec, Erwan; Le Roy, Pascal; Penaud, Aurélie
Our study aims to understand the recurring climatic conditions prevailing during the largest storms reaching NW France (Brittany). These storms are responsible for the breaching of coastal barriers and major flooding of lowlands. In a first part of our work, we examine the morphological impact and stratigraphic record of storm events along Western Brittany rocky coasts, with a special focus on the southern coast of the Bay of Audierne, the most exposed coast of the region. In a second paper ('Middle- to Late-Holocene Storminess in Brittany (NW France): Part II'), we shall focus on the chronology of storm events and their climate forcing conditions. Drilling transects and stratigraphic analyses were first undertaken to constrain chronology, strength and wind direction during the main Holocene storm events. New dates, observations and a relative sea-level (RSL) curve were then used to inform discussion of the necessary climatic and morphologic conditions leading to destructive storm events. Most recorded events appear to be linked with cooling episodes of the Holocene and a RSL close to present. Some storms are clearly responsible for breaching and dune building or remobilisation. We demonstrate that storm frequency and intensity appear to rise in a stepwise manner during the late Holocene. Maximum efficiency is reached during the 'Little Ice Age' with clustered events probably lasting several days, but major storms also occurred immediately prior to the 'Medieval Warm Period'. We suggest that recent coastal dune building from c. ad 1100 until now, despite a sea level close to present and continuously rising, may be a direct consequence of the restoration of beaches after periods of recurrent storminess. This building activity often occurred during dry negative North Atlantic Oscillation (NAO) events, in connection with the available sedimentary supply.